2009
DOI: 10.1007/s00426-008-0223-x
|View full text |Cite
|
Sign up to set email alerts
|

Implementation intentions about nonfocal event-based prospective memory tasks

Abstract: Implementation intentions are detailed and systematic plans that are developed during intention formation. We compared two different implementation intentions to standard event-based prospective memory instructions using three different kinds of intentions. Two of these intentions involved nonfocal cues whereas the remaining intention was about specific, focal cues. Implementation intentions dramatically increased detection performance for the nonfocal intentions. Because the exact cues could not be specified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
83
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(96 citation statements)
references
References 29 publications
12
83
1
Order By: Relevance
“…The additional specification of the behavior within the then-component is assumed to build a strong cue-behavior link (Webb & Sheeran, 2003) that may support later memory retrieval. Several studies investigated the influence of implementation intentions on PM in other populations with reduced planning abilities such as older adults (Chasteen, Park, & Schwarz, 2001;McDaniel, Howard, & Butler, 2008;McFarland & Glisky, 2011;Meeks & Marsh, 2010), and across the lifespan (Zimmermann & Meier, 2010). Overall, results showed that implementation intentions reduce existing age differences in PM through automatically triggering prospective remembering.…”
mentioning
confidence: 84%
“…The additional specification of the behavior within the then-component is assumed to build a strong cue-behavior link (Webb & Sheeran, 2003) that may support later memory retrieval. Several studies investigated the influence of implementation intentions on PM in other populations with reduced planning abilities such as older adults (Chasteen, Park, & Schwarz, 2001;McDaniel, Howard, & Butler, 2008;McFarland & Glisky, 2011;Meeks & Marsh, 2010), and across the lifespan (Zimmermann & Meier, 2010). Overall, results showed that implementation intentions reduce existing age differences in PM through automatically triggering prospective remembering.…”
mentioning
confidence: 84%
“…Yet, future PM research might vary the time and dosage for the different training types to evaluate whether this affects PM training outcomes. Likewise, future PM studies might compare a 4-week training protocol (as used in the present study) with a single training session (as used in prior PM training studies targeting PM intention encoding [5, 9-11, 14-20], in which the encoding strategy was presented to participants only once and was not trained in several sessions during a longer amount of time as in our study). Another possible target for future PM studies might be the investigation of other populations by, e.g., comparing healthy individuals with those with cognitive impairments regarding the effectiveness of imagery and rehearsal PM training.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of PM strategies targeting PM encoding in the intention-formation phase, implementation intentions have been studied most often [9-11]. This approach is based on goal-directed verbalization of intentions in a “If x arises, then I will perform y” manner [12, 13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned earlier, the completion of time based tasks is unlikely to be automatically triggered when the relevant times arise, as the clock is not focal to the on-going activity. Although imagining could on one hand enhance the use of time monitoring by somehow increasing the perceived importance of the task (see Meeks and Marsh, 2010), it is also feasible that imagining enhanced the actual memory for the times at which the tasks needed to be carried out. Indeed the superiority of the social drinker group's performance on irregular event based tasks compared to irregular time based tasks in the pre-imagining condition indicates that new times were harder to commit to memory than new events, and thus that imagining somehow enhanced retention.…”
Section: The Effects Of Imagining On Pm Performancementioning
confidence: 99%